A network perspective on assessing system architectures: Foundations and challenges. Issue 6 (30th October 2019) - Potts, Matthew W.; Sartor, Pia; Johnson, Angus; Bullock, Seth
Abstract: Organizations are increasingly faced with the challenge of architecting complex systems that must operate within a System of Systems context. While network science has offered usefully clear insights into product and system architectures, we seek to extend these approaches to evaluate enterprise system architectures. Here, we explore the application of graph‐theoretic methods to the analysis of two real‐world enterprise architectures (a military communications system and a search and rescue system) and to assess the relative importance of different architecture components. For both architectures, different topological measures of component significance identify differing network vertices as important. From this, we identify several significant challenges a system architect needs to be cognisant of when employing graph‐theoretic approaches to evaluate architectures; finding suitable abstractions of heterogeneous architectural elements and distinguishing between network‐structural properties and system‐functional properties. These challenges are summarized as five guiding principles for utilizing network science concepts for enterprise architecture evaluation.